Dual (thermo-/pH-) responsive P(NIPAM-co-AA-co-HEMA) nanocapsules for controlled release of 5-fluorouracil. Issue 12 (2nd December 2021) - Zhang, Wei-Jin; Yan, Yong-Zhu; Nagappan, Saravanan; He, Shanshan; Ha, Chang-Sik; Jin, Yu-Shun
Abstract: Dual-responsive nanocapsules of poly (N-isopropyl acrylamide (NIPAM)-co-acrylic acid (AA)-co-2-hydroxyethylmethacrylate (HEMA)) were synthesized by precipitation polymerization. The dual (temperature- and pH-)-responsive nanocapsules were fabricated using NIPAM as a temperature-sensitive monomer, AA as a pH-responsive monomer and 5-fluorouracil (5-FU) as a model drug. The P(NIPAM-co-AA-co-HEMA) nanocarrier had a hollow nanocapsule structure with average diameter of about 70 nm and a shell thickness of about 10 nm. The nanocarrier exhibited good loading capacity (32.6%) and considerable encapsulation efficiency (57.3%) for 5-FU by physical entrapment. The zeta potentials of nanocapsules were observed from −30.7 to −35.2 mV after the incorporation of 5-FU. The cumulative release of nanocapsules reached at 88.7% (37 °C, pH 5.8). The overall drug release performance revealed that the drug release behavior was efficient, sustainable and stable at 37 °C and pH 7.4. In addition, the release mechanism analysis suggested that the drug release behavior is more dependent on pH than temperature. Graphical Abstract: UF0001